Sense of ownership is linked to the speed of visuomotor adaptation in virtual reality but not to generalization, intermanual transfer, or aftereffects - Johanna Gerken; Opher Donchin; Thomas Abel; Susen Werner (Scientific Reports)
Abstract Visuomotor adaptation, a form of motor learning in which familiar movements are adjusted to changes in visual feedback, has been widely studied in 2D settings. Testing this in virtual reality (VR) enables the exploration of 3D movements, offering a more realistic representation of motor behavior in daily tasks. While some studies have compared adaptation in 2D and 3D, none have examined the effect of visual feedback type. We compared adaptation via either a virtual hand or a cursor as feedback. The participants adapted to a visuomotor rotation while reaching in VR, and we assessed adaptation performance, spatial generalization, intermanual transfer, aftereffects, and sense of agency. Hand-based feedback facilitated faster adaptation, likely due to a stronger sense of agency, as indicated by a positive correlation between agency ratings and the adaptation rate. However, spatial generalization, intermanual transfer, and aftereffects did not differ between feedback types, suggesting that adaptation remained context-dependent and that the feedback modality did not influence the balance between explicit and implicit learning. We observed high intermanual transfer (~ 80%), driven primarily by explicit adaptation, which is consistent with previous 2D studies. These findings provide insights into visual feedback’s role in sensorimotor learning and have implications for rehabilitation and skill training in immersive environments.